Leiomyoma of Broad Ligament Mimicking Ovarian Malignancy– Report of a Unique Case - Mallick, D; Saha, M; Chakrabarti, S; Chakraborty, J (Kathmandu University Medical Journal, 2015)
Tumors of the broad ligament are uncommon. Leiomyoma, which is the commonest female genital neoplasm, is also the most common solid tumor of the broad ligament. Leiomyomas affect 30% of all women of reproductive age but the incidence of broad-ligament leiomyoma is